Answer:
In order to read the degrees of an angle with a protractor, you must first determine if the angle is acute or obtuse. If it is acute, you use the measurement of the smaller number on the protractor. If it is obtuse, you use the larger measurement on the protractor.
For example, the measurement of the angle in question 1 seems to be about 74 degrees.
Answer:
original price = $30.00
Step-by-step explanation:
note that the original price is 100% , then
1% = $1.50 ÷ 5 = $0.30 , so
100% = 100 × $0.30 = $30.00
Answer:
69 need to be added
Step-by-step explanation:
1300 +69 = 1369
37 ² = 1,369
square root of 1,369 is 37
Step-by-step explanation:
OK, let's assume it this way:
<em>Sn=1.1!+2.2!+3.3!+...+n.n!</em><em>=</em><em>(</em><em>2</em><em>‐</em><em>1</em><em>)</em><em>.</em><em>1</em><em>!</em><em>+</em><em>(</em><em>3</em><em>-</em><em>1</em><em>)</em><em>.</em><em>2</em><em>!</em><em>+</em><em>(</em><em>4</em><em>-</em><em>1</em><em>)</em><em>3</em><em>!</em><em>+</em><em>.</em><em>.</em><em>.</em><em>+</em><em>(</em><em>(</em><em>n</em><em>+</em><em>1</em><em>)</em><em>-</em><em>1</em><em>)</em><em>.</em><em>n</em><em>!</em>
Sn=1.1!+2.2!+3.3!+...+n.n!=(2‐1).1!+(3-1).2!+(4-1)3!+...+((n+1)-1).n!<em>=</em><em>(</em><em>2</em><em>.</em><em>1</em><em>!</em><em>-</em><em>1</em><em>!</em><em>)</em><em>+</em><em>(</em><em>3</em><em>.</em><em>2</em><em>!</em><em>-</em><em>2</em><em>!</em><em>)</em><em>+</em><em>(</em><em>4</em><em>.</em><em>3</em><em>!</em><em>-</em><em>3</em><em>!</em><em>)</em><em>+</em><em>.</em><em>.</em><em>.</em><em>+</em><em>(</em><em>(</em><em>n-1</em><em>)</em><em>n</em><em>!</em><em>-</em><em>n</em><em>!</em><em>)</em><em>=</em><em>(</em><em>2</em><em>!</em><em>-</em><em>1</em><em>!</em><em>)</em><em>+</em><em>(</em><em>3</em><em>!</em><em>-</em><em>2</em><em>!</em><em>)</em><em>+</em><em>(</em><em>4</em><em>!</em><em>-</em><em>3</em><em>!</em><em>)</em><em>+</em>
Sn=1.1!+2.2!+3.3!+...+n.n!=(2‐1).1!+(3-1).2!+(4-1)3!+...+((n+1)-1).n!=(2.1!-1!)+(3.2!-2!)+(4.3!-3!)+...+((n-1)n!-n!)=(2!-1!)+(3!-2!)+(4!-3!)+<em>.</em><em>.</em><em>.</em><em>+</em><em>(</em><em>n</em><em>+</em><em>1</em><em>)</em><em>!</em><em>-</em><em>n</em><em>!</em><em>=</em><em>(</em><em>n</em><em>+</em><em>1</em><em>)</em><em>!</em><em>-</em><em>1</em><em>!</em><em>=</em><em>(</em><em>n</em><em>+</em><em>1</em><em>)</em><em>!</em><em>-</em><em>1</em>
and boom problem solved